Genotoxic Effects on Gas Station Attendants in South-southeastern México due to Prolonged and Chronic Exposure to Gasoline - Rebeca I. Martínez-Salinas; Irene Sánchez-Moreno; Juan J. Morales López; Benito Salvatierra Izaba; Everardo Barba Macías; Anahí Armas-Tizapantzi; Arturo Torres-Dosal (Elsevier, 2024)
Background: Gasoline, a complex mixture of volatile organic compounds is classified as possibly carcinogenic to humans. Gasoline station attendants, consistently exposed to its hazardous components, may face genotoxic effects. This study aimed to assess the influence of varying work shift durations on DNA damage in gasoline station attendants. Methods: Ninety individuals from three locations in southern México were studied. Peripheral blood mononuclear cells (PBMCs) were isolated, and DNA damage was assessed using the comet assay. Demographic, occupational, and lifestyle data were collected. Statistical analyses included t-tests, ANOVA, and Pearson correlation. Results: Significant differences in DNA damage parameters were observed between exposed and unexposed groups. The impact of tobacco, alcohol, and exercise on DNA damage was negligible. Extended work shifts (12 and 24 hours) showed heightened DNA damage compared to 8-hour shifts and the unexposed group. A novel finding revealed a modest but significant correlation between DNA damage and job seniority. Conclusion: The study highlights the intricate relationship between occupational exposure to gasoline components, DNA damage, and work shift lengths. Extended shifts correlate with heightened genotoxic effects, emphasizing the importance of personalized safety measures. The significant correlation between DNA damage and job seniority introduces occupational longevity as a determinant in the genetic health of gasoline station attendants. This discovery has implications for implementing targeted interventions and preventive strategies to safeguard workers' genetic integrity throughout their years of service. The study calls for further exploration of unconsidered factors in understanding the multifactorial nature of DNA damage in this occupational setting.